HUBUNGAN KEMAMPUAN KECEPATAN DAN KELINCAHAN DENGAN KETERAMPILAN DRIBBLING PEMAIN SEPAK BOLA DIKLAT CIREBON UNITED U14 - Hadi, Risa; Risa Hadi; Harun; Riski Tri Yadi (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2025)
Cirebon United U14 Training players experience difficulties in dribbling where the ball often falls out or is not well controlled when passing the opponent. Dribbling skills are not only influenced by training but also by potentially influenced by physical abilities such as speed and agility. This study aims to determine the relationship between speed and agility abilities with dribbling skills of Cirebon United U14 Training soccer players. This study used a cross-sectional correlational method with a sample of 30 players aged 14, with a body weight of 50.73 ± 7.34 kg, a height of 164.23 ± 6.94 cm, a body mass index of 18.7 ± 1.7 kg / m2 and training experience of 5.70 ± 1.51 years. The data collection was obtained through tests and measurements consisting of: speed ability test (20m sprint), agility ability (T-test Agility) and dribbling skills (zigzag dribbling). Data were analyzed using the Pearson correlation test with the help of SPSS software. The results of this study indicate that there is a significant relationship between agility ability (T-test Agility) and dribbling skills with a correlation value of 0.008 (<0.05). However, there is no significant relationship between speed ability and dribbling skills with a correlation value of 0.165 (>0.05) in Cirebon United U14 Training players. There is a significant relationship between agility ability (T-test Agility) and dribbling skills of Cirebon United U14 Training soccer players with a correlation value of 0.008 (<0.05).